Pengaruh Word Of Mouth dan Customer Relationship Management Terhadap Minat Beli Ulang PT. Hasana Makmur Sejati Jaya Medan - Stephanie Stephanie; Syawaluddin Syawaluddin; Aidil Putra; Thomas Sumarsan Goh (Universitas Batanghari, 2022)
PT. Hasana Makmur Sejati Jaya Medan is: a company engaged in the sale of glue. PT. Hasana Makmur Sejati Jaya itself is a distributor of Fox glue. Customer repurchase interest has decreased from year to year. The products offered by the company have not created a conversation that can create or create an impression in the minds of customers. The implementation of customer relationship strategies by companies to consumers is still lacking. This research uses quantitative descriptive research. The research population that will be used in the study is all customers who buy from the company as many as 74 customers. Determination of the research sample using saturated sampling. Simultaneously there is a significant influence between word of mouth and CRM strategy on the repurchase intention of PT. Hasana Makmur Sejati Jaya. While partially found the variable word of mouth has a significant effect on the repurchase intention of PT. Hasana Makmur Sejati Jaya. Partially, it was found that the CRM strategy variable had a significant effect on the repurchase intention of PT. Hasana Makmur Sejati Jaya.